Evaluasi Kesehatan Masyarakat Melalui Pemeriksaan Asam Urat : Studi Lapangan Kelurahan Anduonohu - Irma Yunawati; Tirsa Ayudya M; Nur Hikmatul Alia; Yusmiati Yusuf; Imanuel Saulanda; Fitriani Iqbal; Arianti Arianti; Wa Ode Salma; Nurhasriana Jufri; Nabil Al Mahmud (The Journal General Health and Pharmaceutical Sciences Research, 2024)
Gout is a metabolic disorder whose prevalence continues to increase in society. This study aims to evaluate public health by examining uric acid levels in the local population and analyzing the risk factors that influence it. The research method used is a quantitative approach with field surveys and checking uric acid levels using a portable diagnostic tool. Data was collected from 50 respondents who were randomly selected in the Anduonohu ​​sub-district area. The research results showed that the average respondent had uric acid levels above the normal threshold. The main risk factors identified include consumption of foods high in purine, lack of physical activity, and family history of similar diseases. This study underlines the importance of regular check-ups and public education about healthy lifestyles to prevent increased uric acid levels. Community-based interventions are recommended to reduce the prevalence of this disease. It is hoped that this research can become a reference in planning more effective public health programs.